Raspberry PI - Atnoorkar Md Haris; Sajid Shaikh (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Now-a-day’s, computer is not only a luxury but also a necessity for every person in todays world. Raspberry pi is a credit-card sized computer aimed at providing a computer to every person in the world. Raspberry Pi is intended to provide a base on which kids can learn programming while enthusiasts can do different types of commercial programming. It serves as an efficient base due to its low cost and the number of interfaces available. The Raspberry Pi can be used instead of a personal computer, but with some limitations due to its limited processing power. In this paper we will learn about the basics, hardware and its implementation